Depression mediates the association between health literacy and health-related quality of life after myocardial infarction - Kirchberger, Inge; Fischer, Simone; Raake, Philip; Linseisen, Jakob; Meisinger, Christine; Schmitz, Timo (Frontiers in Psychiatry, 2024)
Introduction: So far, health literacy (HL) and its related factors in patients with acute myocardial infarction received little attention. Thus, the objective of this study was to investigate the associations between the different dimensions of HL and disease-specific health-related quality of life (HRQOL), and factors that may affect these relations in patients after acute myocardial infarction (AMI).Methods: All survivors of AMI between June 2020 and September 2021, from the Myocardial Infarction Registry Augsburg (n=882) received a postal questionnaire on HL (Health Literacy Questionnaire (HLQ)), HRQOL (MacNew Heart Disease HRQOL questionnaire) and depression (Patient Health Questionnaire). From the 592 respondents, 546 could be included in the analysis. Multivariable linear regression models were performed to investigate the associations between the nine subscales of the HLQ and the total score and three subscales of the MacNew questionnaire. A mediation analysis was performed to estimate direct and indirect effects of HL on HRQOL taking into account the mediating effect of depression.Results: In the sample of 546 patients (72.5% male, mean age 68.5 ± 12.2 years), patients with poor education showed significantly lower HLQ scores. Significant associations between the subscales of the HLQ and the MacNew were found, which remained significant after adjustment for sociodemographic variables with few exceptions. More than 50% of the association between HL and HRQOL was mediated by depression in seven HLQ subscales and a complete mediating effect was found for the HLQ subscales 'Actively managing my health' and ‚Appraisal of health information'. Discussion: Depression mediates the associations between HL and disease-specific HRQOL in patients with myocardial infarction.